Corrigendum and Addendum: Helium flux effects on bubble growth and surface morphology in plasma-facing tungsten from large-scale molecular dynamics simulations (2019 Nucl. Fusion59 066035). (7th October 2020) - Hammond, Karl D.; Lee, Brandon F.; Naeger, Ian V.; Widanagamaachchi, Wathsala; Lo, Li-Ta; Maroudas, Dimitrios; Wirth, Brian D.
Abstract: Two of the simulations discussed in a prior article (Hammond et al 2019 Nucl. Fusion 59 066035) were affected by a simulation glitch. We repeated the affected calculations and discuss them here. The overall conclusions are essentially unchanged, though the details are different. In particular, observations that we referred to as 'concerted bursting' were caused primarily by non-physical heating and cooling applied by the thermostat after most atoms' velocities were deleted (for reasons that are not known for certain). The phenomenon of one bubble bursting and causing another nearby bubble to burst does exist, though its effects are much less spectacular in the absence of non-physical driving forces. The observation of an interconnected network of sub-surface cavities formed by burst bubbles is real, and the observation of holes on the surface 1–2 nm in diameter is also confirmed.